The Effect of Corporate Social Responsibility Disclosure on Company Value Moderated by Profitability in Mining Sector Companies Listed on the IDX in 2020–2024 - Haiku Katyusha Abdillah; Acep Komara (CV. Media Digital Publikasi Indonesia, 2026)
This study aims to analyze the effect of Corporate Social Responsibility (CSR) disclosure on the value of companies with profitability as a moderation variable in mining sector companies listed on the Indonesia Stock Exchange (IDX) for the 2020–2024 period. The independent variable in this study is CSR disclosure which is measured using the Corporate Social Responsibility Disclosure Index (CSRDI) based on the Global Reporting Initiative (GRI) guidelines. The dependent variable is the value of the company that is proxied using Tobin's Q, while profitability as a moderation variable is measured by Return on Assets (ROA). This study uses a quantitative approach with the Moderated Regression Analysis (MRA) method. The data used is secondary data obtained from the annual report and sustainability report of the sample company. The results of the study show that CSR disclosure has a significant effect on company value in a negative direction. Profitability (ROA) has a significant effect on the company's value in a positive direction. However, the results of testing the CSR×ROA interaction variables showed that profitability was not able to moderate the relationship between CSR disclosure and company value. These findings indicate that the capital market still assesses CSR as a cost or expense that has the potential to lower the valuation of mining companies, while profitability remains the main factor that increases the value of companies. This research provides theoretical contributions in the development of Stakeholder Theory and Signaling Theory in the context of the Indonesian mining industry, as well as provides practical implications for companies and investors related to CSR disclosure strategies and strengthening profitability performance.